The effect of the guided inquiry model on students' mathematics learning outcomes based on creativity levels - Mei Yunika Puteri; Sri Sutarni (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
Student achievement in mathematics in Indonesia remains relatively low, highlighting the need for learning models that can foster engagement and deeper understanding. This study investigates the effect of the Guided Inquiry learning model on mathematics achievement by considering the role of student creativity. A quasi-experimental design with a posttest-only control group was employed. The population consisted of all Grade VII students of SMP Negeri 2 Kedawung in the 2024/2025 academic year. Using random sampling, class VIIB was assigned as the experimental group and class VIIE as the control group. Data were collected through tests and questionnaires, and analyzed using normality tests, homogeneity tests, and two-way ANOVA with unequal cells. Balance between groups was established using students' odd-semester final examination scores prior to treatment. The findings revealed that: (1) the Guided Inquiry model was more effective than conventional instruction in improving mathematics achievement, (2) student creativity significantly influenced mathematics achievement, and (3) there was no interaction effect between the Guided Inquiry model and student creativity. These results suggest that the Guided Inquiry model can effectively improve students' mathematics achievement, while creativity contributes independently to learning outcomes.